Pre-Operative versus Postoperative Surgical Analgesia - Ahmed, Hiwa Omer; Muhemad, Ako Ibrahim (Sulaimani Journal for Pure and Applied Sciences, 2008)
Background; postoperative pain remain the most common dilemma for surgical patients, there are many methods for control of pain, either by conventional postoperative analgesia or preoperative analgesia. The aim; is to evaluate the benefit of Diclofenac as pre-operative analgesia in comparison to the postoperative conventional treatments. Methods and Patients; this study includes patients of different age and sex groups, underwent different elective and emergency surgical operations, They divided in to two groups: - Group A (100 patients): controlled group, were received pre-operative analgesia. - Group B (100 patients): compared group, were received the conventional analgesia. Results; thirty eight percent of patients in group A have significant pain versus eighty six percent of the patients in group B (P value 0.0000) Preoperative analgesia as single dose of Diclofenac is more effective in control of postoperative pain than conventional postoperative analgesia. Conclusion; we could say that the pre-operative (pre-emptive) analgesia is safe, feasible, well tolerant, less costly and more effective for the control of different types of the surgical pain.
Keywords: pain; preemptive analgesia; conventional analgesia Diclofenac